A new Brazilian species of Loxandrus LeConte, 1852, with description of immatures and notes on natural history (Coleoptera: Carabidae: Loxandrini) - Costa, Cleide; Vanin, Sergio A.; de Carvalho, Thiago R. (Zootaxa, 2011)
Loxandrus oophagus sp. nov. is described (type-locality: Uberlândia, State of Minas Gerais, Brazil). Larvae, pupae and adults of the new species of the carabid beetle were collected on foam nests of the anuran Leptodactylus fuscus (Schneider, 1799) in the surroundings of Uberlândia, 18º55S, 48º17W (Brazil, Minas Gerais), at 750 m altitude. The new species is compared with the similar Loxandrus quinarius Will & Liebherr, 1997, only known from Santa Cruz, Bolivia, differing by the morphology of tarsomeres. Larvae prey on anuran eggs. Description of the immatures and the natural history of the species are provided. The larva differs from the known larvae of Loxandrus species mainly by being eruciform, glabrous and depigmented, its small head and legs, and the lack of stemmata and urogomphi, representing an unusual last instar type among the Carabidae.